Respuesta :

Answer:

Inverse function: If a function f(x) is mapping x to y, then the inverse function of f(x) maps back y to x

Given that: [tex]y = \frac{2}{3}x -6[/tex]

Interchange the variable x and y;

[tex]x = \frac{2}{3}y -6[/tex]

Add 6 to both sides we get;

[tex]x +6= \frac{2}{3}y -6+6[/tex]

Simplify:

[tex]x+6= \frac{2}{3}y[/tex]

Multiply both sides by [tex]\frac{3}{2}[/tex] we get;

[tex]\frac{3}{2}(x+6) = y[/tex]

or

[tex]y = \frac{3}{2}x+ 9[/tex]

Therefore, the inverse of [tex]y = \frac{2}{3}x-6[/tex] is,

[tex]y = \frac{3}{2}x+ 9[/tex]